Analysis of Patient Service Quality with IOM Indicators in the Dental Polyclinic of Bhayangkara Hospital, Polri Education and Training College - Astriany.H, Vivi; Kodyat, Alih Germas; Trigono, Ahdun; Chandra, Andy (International Journal of Business, Law, and Education, 2026)
High-quality healthcare services are essential to ensure patient satisfaction and sustainable hospital performance. This study aims to analyze patient service quality at the Dental Clinic of Bhayangkara Lemdiklat Police Hospital using the Institute of Medicine (IOM) framework, which includes six dimensions: safety, effectiveness, patient-centeredness, timeliness, efficiency, and equity. A quantitative descriptive design with a survey approach was employed. A total of 94 patients were selected through purposive sampling. Data were collected using a structured questionnaire measuring patients’ expectations and perceived performance. The instrument was tested for validity and reliability, and the data were analyzed using descriptive statistics, paired sample t-tests, regression analysis, and Importance–Performance Analysis (IPA). The results indicate that overall service quality is perceived as good, particularly in effectiveness, safety, and patient-centered care, which obtained the highest mean scores. However, gaps remain in equity, timeliness, and efficiency. Equity showed the lowest mean value and the highest variability, suggesting that patients still perceive unequal treatment and service procedures. Paired sample correlations revealed strong and significant relationships among the IOM dimensions, implying that improvements in one aspect may positively influence others. Regression and ANOVA results indicate that service quality does not significantly differentiate patient types (general and BPJS). The IPA analysis places effectiveness, safety, and patient-centeredness in the “maintain performance” quadrant, while timeliness, efficiency, and equity require strategic improvement. These findings highlight the importance of continuous quality enhancement, particularly in ensuring fair, timely, and efficient dental services